From Sparse Features to Transformers: A Statistical Evaluation of TF-IDF, FastText, and IndoBERT for Sentiment Classification of Indonesian Travel App Reviews - Claudian Tikulimbong Tangdilomban; Syaifullah Yusuf Ramdhan; Muhammad Rizal; Cici Suhaeni; Bagus Sartono (Politeknik Negeri Batam, 2026)
This study compares three text representation techniques, namely TF-IDF, FastText, and IndoBERT, in the sentiment classification task of Indonesian-language user reviews of travel applications. The dataset consists of 4.000 reviews from Traveloka and Tiket.com, collected through Google Play Store scraping and manually annotated with sentiment labels. Each representation technique was combined with three classification algorithms, namely Support Vector Machine, Logistic Regression, and Random Forest, resulting in nine experimental configurations. The evaluation was conducted using stratified 5-fold cross-validation with macro F1-score as the primary metric, supported by hyperparameter tuning using GridSearchCV, paired t-test statistical analysis, and Cohen’s d effect size measurement. The evaluation results indicate that IndoBERT generally achieved the best performance compared to TF-IDF and FastText. The best configuration was obtained by IndoBERT with Logistic Regression, achieving an F1-score of 0.9261 after tuning. The statistical test showed that the performance differences among text representations were statistically significant, with large effect sizes in the comparison between IndoBERT and TF-IDF (d = −1.36) and between IndoBERT and FastText (d = −1.10). Nevertheless, TF-IDF combined with Logistic Regression and SVM remained competitive, achieving an F1-score of approximately 0.892 after tuning, making it a lightweight and interpretable alternative. This study concludes that the quality of text representation has a more dominant influence on sentiment classification performance than the complexity of the classification algorithm.